The path to power - Thatcher, Margaret (New York : HarperCollins, 1995)
In The Downing Street Wars, Margaret Thatcher gave her own account of her prime ministership from 1979 to 1990. That book justly became a bestseller all over the world. Now, in The Path to Power, she writes for the first time about her personal life, about the formation of her character and values, and about the training and experiences which led to the 1979 election victory.
Includes index.
Originally published: United Kingdom : HarperCollins U.K.
0
Keywords: Women prime ministers -- Great Britain